Analisis Daya Saing Ekspor Karet Alam Indonesia dalam Perdagangan ke Pasar Internasional Periode 2015-2024 dengan Pendekatan RCA, RSCA, Growth RCA, dan EPD - Defeera Mulaftzal Jannah; Rizqi Muttaqin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study analyzes the export competitiveness of Indonesia’s and Thailand’s natural rubber in international markets over the period 2015–2024 using a quantitative descriptive approach. The research employs four complementary indicators—Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), Growth RCA, and Export Product Dynamic (EPD)—based on secondary time‑series data for export value, export volume, and total trade drawn from official international statistics. The results show that both Indonesia and Thailand possess strong comparative advantages (RCA > 1 and positive RSCA). However, Indonesia’s RCA values display a significant declining trend after 2018, while Thailand’s performance remains relatively more stable. Growth RCA analysis indicates that Indonesia experienced periods of increasing comparative advantage, but the growth was not sustainable. Based on EPD analysis, Indonesia’s natural rubber exports were more frequently categorized as retreat, whereas Thailand more consistently achieved the rising star position in recent years. These findings highlight the need for downstream industrialization, productivity improvement, and stronger sustainability standards to enhance Indonesia’s natural rubber export competitiveness.